A Brief Probe into Big Data Architecture of Enterprise - Yongfeng Wang; Xinzhou Cheng; Jie Gao (Dianxin kexue, 2015)
While data value is deeply appreciated nowadays, enterprises are considering about extracting and digging data value. The architecture of big data was analyzed from the aspect of enterprises. And the characteristic and the application of data were also deeply considered.